Upregulation of interferon-γ response genes in monocytes and T cells identified by single-cell transcriptomics in patients with anti-citrullinated peptide antibody-positive early rheumatoid arthritis - Hong, Bong-Ki; You, Sungyong; Kim, Jung Gon; Kim, Minhyung; Lee, Naeun; Lee, Kijun; Baek, In-Pyo; Ju, Ji Hyeon; Kim, Wan-Uk; Kim, Ho-Youn (Frontiers in Immunology, 2025)
IntroductionOur aim was to investigate the insufficiently understood differences in the immune system between anti-citrullinated peptide antibody (ACPA)-positive (ACPA+) and ACPA-negative (ACPA-) early rheumatoid arthritis (eRA) patients.MethodsWe performed multiple cytokine assays using sera from drug-naïve ACPA+ and ACPA- eRA patients. Additionally, we conducted single-cell RNA sequencing of CD45+ cells from peripheral blood samples to analyze and compare the distribution and functional characteristics of the cell subsets based on the ACPA status.ResultsSerum concentrations of interferon-γ (IFN-γ) and interleukin (IL)-12 were higher in ACPA+ eRA than in ACPA- eRA. Single-cell transcriptome analysis of 37,318 cells identified 17 distinct cell types and revealed the expansion of IL1B+ proinflammatory monocytes, IL7R+ T cells, and CD8+ CCL4+ T cells in ACPA+ eRA. Furthermore, we observed an enrichment of IFN-γ response genes in nearly all monocytes and T cells of ACPA+ eRA subsets. Heightened interactions between IFN-γ and IFN-γ receptors were observed in ACPA+ eRA, particularly between monocytes and T cells. We examined IFITM2 and IFITM3 as potential key markers in ACPA+ eRA given their pronounced upregulation and association with the IFN response. Specifically, the expression of these genes was elevated in IL1B+ proinflammatory monocytes (likely M1 monocytes), correlating with serum IFN-γ levels.DiscussionCompared to ACPA- eRA, ACPA+ eRA showed higher serum IFN-γ and IL-12 levels, upregulated IFN-γ response genes, and enhanced IFN-γ-driven monocyte-T cell interactions. These distinct immune features of the peripheral circulation in ACPA+ eRA suggest a role for type 1 helper T cell-related immunity in its pathogenesis.